Modelling external pelvic dimensions as a screening tool for cephalopelvic disproportion - Iswara, Denny; Kusmiyati, Yuni; Apay, Serap Ejder (Jurnal Kesehatan Ibu dan Anak, 2024)
Cephalopelvic disproportion (CPD) remains one of the leading causes of labor complications and cesarean deliveries, particularly in low-resource settings where pelvimetric assessment is limited. The absence of a simple, accurate, and non-invasive screening tool in primary healthcare complicates early detection and management. This study aimed to design and evaluate an external pelvic measurement tool to identify women at risk for CPD. This was a quantitative case-control study involving 60 postpartum women at Dr. Sardjito Hospital, Yogyakarta, Indonesia, between 2018 and 2023. The case group included 30 women diagnosed with CPD, while the control group comprised 30 women with spontaneous vaginal deliveries. External pelvic measurements were conducted at the Michaelis rhomboid and other anatomical landmarks (AB, AD, CB, CD, BD, AC) using standardized procedures. Sociodemographic variables were controlled through matching by age, parity, and gestational age. Significant differences were observed in external pelvic dimensions between the case and control groups. The average AB, AD, CB, and CD distances were consistently shorter in the CPD group (mean ~5.7–5.8 cm) compared to the control group (mean ~6.8 cm). Pelvic circumference and distances such as distansia cristarum and Boudeloque diameter were also smaller in CPD cases. These findings suggest that women with smaller external pelvic dimensions are at higher risk for CPD. The study highlights that specific external pelvic measurements, particularly within the Michaelis rhomboid area, have potential as practical indicators for early CPD detection. Implementing this tool in antenatal care, especially in primary healthcare settings, may improve screening, guide referral decisions, and reduce the risk of obstructed labor.